Development of a culturally integrated Mandarin as a foreign language module for novice learners in polytechnics / Chan Suet Fong - Chan , Suet Fong (2018)
Globalization has resulted in the need for foreign language education to focus on the development of intercultural communicative competence (ICC). However, in Malaysian higher education institutions (HEIs), ICC does not seem to be integrated in the curriculum of Mandarin as a foreign language (MFL) courses. Hence, the aim of this study is to develop a Culturally Integrated Mandarin as a Foreign Language (CIMFL) module for the selected HEI, a Polytechnic with novice MFL learners. A Design and Development Research (DDR) approach comprising of three phases, was employed. In Phase 1, content analysis of cultural and intercultural elements in seven MFL textbooks used in public HEIs, and an assessment of the ICC level of 31 MFL students from a polytechnic using the Student’s ICC Self Assessment (SISA) instrument, was done. The findings indicated insufficient cultural and intercultural elements were used in these textbooks. The scores from SISA indicated a low level of ICC for intercultural knowledge (M = 2.49, SD = .806) and skills (M = 2.54, SD = .805). Hence, there was a need for a module to enhance students’ ICC. Phase 2 involved design and development of the CIMFL module. The learning outcomes (LO), cultural and intercultural elements and instructional strategies for the module were determined from interviews of a panel of seven experts in the field of MFL and ICC. The module elements were determined from the emergent themes in the interviews transcripts. The module was developed and validated by experts for implementation in Phase 3. The usability of the module for promoting students’ ICC was evaluated in Phase 3 by assessing students’ post-course ICC level, and through teacher’s interview and student survey. The module was implemented with the 31 MFL students from Phase 1. Data from transcripts of teacher’s interviews and analysis of students’ feedback survey were analyzed for effectiveness and usability of the module in promoting ICC. Students’ post ICC level was identified through SISA (Post-Course) and ICC formative assessment. The analysis from the class teacher and students’ feedback on the module indicated the module’s strengths in terms of content and instructional strategies. A Wilcoxon Signed-Ranks Test was run for SISA as one of the variables was not normally distributed. The output indicted that the post-test scores for students’ ICC were significantly higher than pre-test scores, for knowledge, skills and attitudes (Z = 49, p < .00), and awareness (Z = 49, p < .00). Students’ ICC formative assessments displayed medium to high levels of ICC in knowledge, skills, attitudes and awareness which comprised of Intercultural Discussion and Reflections, Cultural Discovery, Cultural Quizzes and Intercultural Communicative Task. The result implied that the CIMFL module was effective in enhancing students’ ICC. The findings indicated that the CIMFL module could be used to improve ICC among MFL novice learners in other Polytechnics. This culturally-integrated framework of design for MFL could be used for developing curriculum and resources such as textbooks for Polytechnics and other HEIs. It could also be used for developing other ICC modules for other languages.